The Notion of Coopetition-Based Open-Innovation in Business Practices: A Model to Accelerate Firm Performance - Avotra, Andrianarivo Andriandafiarisoa Ralison Ny; Chengang, Ye; Said, Kmashi Said Mohamed; Chu, Chunhong; Xiang, Li (Frontiers in Psychology, 2022)
In today's competitive business market, firms that collaborate on a coopetition basis face obstacles in the form of decision-making, dependency, and trust in their competitor partners. This current study is the only one that has conducted an examining specific investigation of the relationship between Coopetition and Firm Performance; yet, this relationship appears to be unclear due to the impact of trust and dependency on coopetition. This study investigates the impact of coopetition on firm performance by examining the mediating effects of decision making and open innovation on firm performance. This study utilized partial least square structural equation modelling to evaluate the direct and mediated effects of the variables (PLS-SEM). In order to examine the data, 230 valid responses were used. The findings of this study indicate that open innovation has a significant mediation effect between coopetition and firm performance, and that decision making is also an important mediating effect in bridging the relationship between coopetition and firm performance. By considering these mediators, the findings revealed that coopetition has a significant impact on firm performance through the Decision making, but has a significant effect on firm performance through increasing Open innovation. The findings also revealed that Decision making played a significant role in mediating the relationship between Coopetition and firm performance, which in turn specified a statistically significant positive relationship with Decision making. That mediated a positive relation. According to the findings of this research, modern business firms should recognize the relevance of coopetition-based open innovation in their business processes in order to increase their overall performance.